Explication of Some Codes of the Yakut Epos Olonkho Mythological System (Folklore Time and Space) - M. T. Satanar (Научный диалог, 2020)
The relevance of the study is due, on the one hand, to the insufficient knowledge of the semiotics of the Yakut epos olonkho, and on the other, the need to implement a new paradigm of modern science, which involves the convergence of scientific knowledge. It is noted that the fundamental categories in the worldview are the modes of space and time, which in total lead to another mode of being - a chronotope. The subject of this article is the codes of cosmological mythology in the texts of the epic olonkho from the perspective of a peculiar spatio-temporal organization of the epic world of olonkho. The purpose of the study is to decode the elements of mythology, as a result of which “compressed” messages about scientific knowledge that indicate the existence of a single source of typology of culture are found. Particular attention is paid to the variety of codes, the rules for their emergence, taking into account the national characteristics of language and thinking. A systematic approach to the subject of study, structural-semiotic analysis, methods of review and description are used in the study. The novelty of the study is in an attempt to partially solve the problem of the disunity of two types of cultures (folklore and fundamental laws of nature) in the context of a general typology of culture. This study indicates the prospects for further consideration and definition of the elements of a peculiar symbolic-semiotic system of space-time organization in the texts of the Yakut epos olonkho.